ЎҚУВЧИЛАР ТАДҚИҚОТЧИЛИК ВА КАСБИЙ КЎНИКМАЛАРИНИ ТАНҚИДИЙ ФИКРЛАШ ОРҚАЛИ РИВОЖЛАНТИРИШ - Пардабоев, Ж.Э. (SCIENCE and SOCIETY, 2020)
This article discusses the content of the development of research and professional skills of students using critical thinking, the importance of innovative thinking technologies in teaching robotics, modeling, design, programming, the ability to think critically and the process of its formation.
Keywords: research; robotics; professionalism; critical thinking; logical thinking; data collection; disposition